Effects of replacing soybean meal with Giant Mimosa (Mimosa pigra L.) leaf meal in diet on productive performance, carcass characteristics, and apparent digestibility of native chickens (Leung Hang Kao) - Suebsima, Bancha; Lunpha, Areerat; Siriboon, Chawalit (Agriculture and Natural Resources, 2023)
Importance of the work: Giant Mimosa leaf meal (GLM) in poultry diets is a promising approach to improving nutrition and production efficiency. Objectives: To investigate the productive performance and digestibility for Leung Hang Kao chickens fed a diet containing GLM. Materials & Methods: There were 5 groups with varying GLM levels (0%, 5%, 10%,15% or 20%), each with 4 replicates of 10 chickens. In total, 200 chickens were assessed for growth rate and production costs, while 20 chickens were studied for apparent digestibility. At age 16 wk, 40 chickens were examined for carcass characteristics. Results: The diet with 5% GLM (GLM5) resulted in increased body weight, average daily gain and feed conversion ratios in the chickens. The GLM5 chickens had lower feed cost per gain and a higher net profit per bird (p < 0.05). Chickens in the GLM20 group had higher feed intake and total feed cost (p < 0.01). The GLM5 group had highly significantly (p < 0.01) lower total rearing costs and higher net profit return per bird and a significantly (p < 0.05) greater return on investment compared with the GLM10, GLM15 and GLM20 groups. There were no significant differences in carcass characteristics. At age 16 wk, with increased content of GLM in the diet, the digestibility of dry matter, organic matter and crude protein decreased (p < 0.01). Main finding: Compared with the other GLM levels, the GLM5 group showed improved growth and feed efficiency, lower rearing costs and higher net profit and return on investment. The higher GLM content did not affect carcass characteristics, despite changes in digestibility.